2012
DOI: 10.3109/0886022x.2012.660855
|View full text |Cite
|
Sign up to set email alerts
|

Levofloxacin-Induced Delirium: Is It a Dangerous Drug in Patients with Renal Dysfunction?

Abstract: The central nervous system (CNS) toxicity of fluoroquinolones is well known but usually occurs benign. In the literature, there are a few number of severe CNS toxicity cases related to fluoroquinolones. Levofloxacin is a third-generation fluorinated quinolone antibiotic, is the active levo stereoisomer of ofloxacin, and has one of the most favorable adverse reaction profiles. We describe a case of delirium associated with levofloxacin in a 55-year-old man who was hospitalized in our medical clinic for pneumoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…Similar to our two cases, most previous reports establish advanced age and impaired kidney function as risk factors for levofloxacin‐induced neurotoxicity …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Similar to our two cases, most previous reports establish advanced age and impaired kidney function as risk factors for levofloxacin‐induced neurotoxicity …”
Section: Discussionsupporting
confidence: 91%
“…10,14,15 A 55 year old man with pneumonia and acute kidney injury developed acute delirium after receiving a 500 mg daily intravenous dose of levofloxacin for 10 days with resolution of symptoms 48 hours after discontinuing the medication. 15 A 42-year-old woman endured acute delirium with psychosis after 2 days of treatment with oral levofloxacin 500 mg daily for sinusitis. Her psychosis improved with supportive care and drug discontinuation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has one of the most adverse reaction profiles. [3] Levofloxacin is a dangerous drug in patients with renal dysfunction. In this report, pheochromocytoma crisis with nonoliguric acute renal failure was preoperatively controlled by the treatment of α 1 -adrenergic receptor blocking agent.…”
Section: Discussionmentioning
confidence: 99%
“…Most FQs and their metabolites are excreted from kidney by glomerular filtration and tubular secretion . Nephrotoxicity such as crystalluria, interstitial nephritis and acute renal failure has also been reported during therapy with FQs , but the mechanism is still unknown. Previous studies have demonstrated that oxidative stress plays an important factor in the FQs‐induced adverse effects, such as neurotoxic effects and chondrotoxicity .…”
Section: Discussionmentioning
confidence: 99%